The role of DGK1 and DGK2 in Membrane Contact Sites and Stress Tolerance - García Hernández, Selene; Ruiz-López, Noemí; Botella-Mesa, Miguel Ángel (My University, 2023)
All eukaryotic cells present regions where the membranes of two different organelles are very close (10-30 nm) without fusion, mediated by tether proteins. These regions are known as Membrane Contact Sites (MCS). Contact sites between the endoplasmic reticulum and plasma membrane (ER-PM CS) play important roles in communication, lipid and Ca2+ homeostasis. Upon stress perception, phospholipase C (PLC) is activated at the plasma membrane producing diacylglycerol (DAG) and inositol phosphates from the hydrolysis of PIP(4,5)P2 or PI4P. DAG has an amphipathic structure with a hydrophobic region and a small polar head. In normal conditions DAG has a low concentration, 1% of total polar lipids (Gaude et al., 2007). Accumulation of DAG produces a negative curvature stress due to its small polar head that destabilizes the PM (Campomanes et al., 2019; Putta et al., 2016). Thus, DAG concentration must be finely controlled. DAG is phosphorylated by diacylglycerol kinases (DGKs) producing phosphatidic acid (PA). Both, DAG and PA, are important molecules involved in signalling (Arisz et al., 2009). The Arabidopsis thaliana genome contains seven genes encoding DGKs. While most of them are cytosolic (DGK3-DGK7), DGK1 and DGK2 possess a transmembrane domain that anchor them to the ER. Using different approaches we show that DGK1 (AT5G07920) and DGK2 (AT5G63770) form a complex with Synaptotagmin1 (SYT1, At2g20990), a protein tether located at ER-PM CS (Pérez-Sancho et al., 2015). SYT1 is able to bind preferentially DAG (Ruiz-Lopez et al., 2021), which support the idea of being working together with DGK1 and DGK2. DGK1 and DGK2 transcripts increase after cold treatment and a dgk2 mutant shows reduced root growth under low temperature and a low freezing tolerance. Our studies suggest that DGK1 and DGK2 act in concert with SYT1 to regulate the production of PA at ER-PM CS and highlight the importance of these proteins in stress tolerance.
Keywords: Biología molecular - Congresos; DGKs; COLD; Abiotic Stress; Arabidopsis; DAG